Disputed territories : land, culture and identity in settler societies - Trigger, David S. (David Samuel), 1953-; Griffiths, Gareth (Hong Kong University Press, 2003)
"Disputed Territories investigates the significance of land for contesting cultural identities in comparable settler societies. In the regions of Australasia and southern Africa, European visions of landscape and nature have engaged with southern hemisphere environments and the cultures of indigenous peoples. Amid conflicts over land as a material resource, there has also been an intellectual contest over the aesthetic, iconic and cultural meanings of natural forms and species." "Arising from a programme of seminars held at The University of Western Australia, this collection of eminent international authors assembles contributions from anthropology, geography, history and literary studies. The combination of diverse methods and theoretical approaches establishes the ways that land and nature constitute disputed territories in the mind, as well as material resources subject to pragmatic negotiations."--Jacket.